Reproductive biology of the sesarmid crab Armases rubripes (Decapoda, Brachyura) from an estuarine area of the Sahy River, Sepetiba Bay, Rio de Janeiro, Brazil - Lima,Giovana V. (2006)
The aim of this work was to gain knowledge about reproductive biology of the crab Armases rubripes (Rathbun, 1897) from an estuarine area of the Sepetiba Bay. Samples were taken monthly from February 2003 to January 2004 in the Sahy River estuary (22º56'S; 44º01'W), Rio de Janeiro, Brazil. The crabs were collected by hand during 15-minute catch-effort sessions conducted by two people. In the laboratory, the specimens were separated by sex, carapace width was measured and gonadal stage was checked macroscopically. A total of 830 individuals were caught - 304 males, 373 females (60 ovigerous females) and 153 juveniles. The ovigerous females were found almost year-round, except in November and April, showing a continuous reproductive period. They presented a size range from 8.2 to 15.0 mm carapace width (12.1 ± 1.7 mm). Color and macroscopical aspects determined five gonadal stages for males and females (immature, rudimentary, intermediary, developed and resting). First sexual maturity was estimated at 6.5 mm of carapace width for males and 8.1 mm for females. Individual fecundity varied from 200 to 11,460 eggs (4,458 ± 2,739 eggs). Mean egg size was 0.248 ± 0.026 mm, varying from 0.213 to 0.333 mm, while the volume ranged from 0.0051 to 0.0188 mm³ (0.0082 ± 0.0029 mm³).